The Influence Of Reference Group, Brand Image And Internet Marketing On Buying Decision - Moh Khotib (NAROTAMA UNIVERSITY, Indonesia, 2019)
with the development of technology and information as well as the rapid growth and spread of the population today, has an impact on all aspects of human life. One of them is to communicate fluently in conveying information. In marketing products there are several strategies used, such as the use of reference groups, brand image and internet marketing in determining purchasing decisions. The purpose of this study was to determine the effect of reference groups, brand image and internet marketing on purchasing decisions on As card products. The sampling method uses random sampling, with the method of multiple linear linear analysis the research shows that the reference group, brand image and internet marketing have an effect on the As card purchase decision. In this research, it is expected to be able to give a new view in marketing products, especially among the community.